Parasironidae fam. nov., a Cimmerian lineage of Mediterranean Cyphophthalmi (Opiliones), with the description of three new genera and four new species - Karaman, Ivo M.; Mitov, Plamen G.; Snegovaya, Nataly (European Journal of Taxonomy, 2024)
A new family of Cyphophthalmi with disjunct Mediterranean distribution, Parasironidae fam. nov., is proposed. The new family comprises four genera and seven species. Cimmerosiro gen. nov., Tirrenosiro gen. nov. and Ebrosiro gen. nov. are described as new genera, and Tirrenosiro axeli gen. et sp. nov., Cimmerosiro krivolutskyi gen. et sp. nov., C. juberthiei gen. et sp. nov. and C. rhodiensis gen. et sp. nov. as new species. Parasironidae stands out by a set of characteristics that we recognize as predominantly plesiomorphic. These characteristics and the present distribution indicate the great age of the family, probably early Mesosoic. We attribute its origin to the western part of the Cimmerian terrane, and its current distribution and diversification of the major clades to geotectonic events during the Mesozoic. Additionally, a new sensory organ (sensilla) has been discovered in Cyphophthalmi. This organ is located on the pedipalp coxae and is believed to have a potential hygroreceptive function.